RETRACTED ARTICLE: Oil from pumpkin (Cucurbita pepo L.) seeds: evaluation of its functional properties on wound healing in rats - Sana Bardaa; Nihed Ben Halima; Fatma Aloui; Riadh Ben Mansour; Hazem Jabeur; Mohamed Bouaziz; Zouheir Sahnoun (Lipids in Health and Disease)
Abstract Background Increasing natural drug demand for pharmaceutical uses has encouraged scientifics all over the world to explore medicinal plants recognized as efficient remedies. In this context, extracted oil from pumpkin seeds (Cucurbita pepo L.) is an interesting target, as it is composed with prominent pharmacological properties to possible wound healing treatments. Methods The composition and content of certain bioactive constituents of the cold pressed oil obtained from pumpkin seeds (Cucurbita pepo L.) were analyzed and studied for their wound healing properties. Uniform wounds were induced on the dorsum of 18 rats, randomly divided into three groups. The wounds were photographed, and topically treated with saline solution (control group), 0.13 mg/mm2 of a reference drug (“Cicaflora cream®”), and 0.52 μl/mm2 of pumpkin’s oil each 2 days until the first group is completely healing and so far biopsies were histologically assessed. Results The composition and content of tocopherols, fatty acids, and phytosterols were determined. The results showed an excellent quality of pumpkin oil with high content of polyunsaturated fatty acids (Linoleic acid: 50.88 ± 0.106 g/100 g of total fatty acids), tocopherols (280 ppm) and sterols (2086.5 ± 19.092 ppm). High content of these bioactive components were in agreement with an efficient wound healing by the mean of an in vivo study. In fact, morphometric assessment and histological findings revealed healed biopsies from pumpkin oil treated group of rats, unlike untreated group, and a full re-epithelialization with reappearance of skin appendages and well organized collagen fibers without inflammatory cells. Conclusions This study showed the significance of oil from pumpkin seeds (Cucurbita pepo L.) as a promising drug to healing wounds in animal assays. As a whole, pumpkin’s oil would be recommended in the nutritional and medicinal purposes.